APLIKASI GAME EDUKASI PENGENALAN BAHASA INGGRIS BERBASIS ANDROID UNTUK ANAK USIA DINI - John Roni Coyanda; Irawan Irawan; Juhaini Alie (UNIVERSITAS INDO GLOBAL MANDIRI)
Global technological progress requires English as a second language to be learned after Indonesian. Introduces English to children from an early age will facilitate the process of adapting itself to the advancement of information technology which requires knowledge of the English language in the future. Introduce English language in early childhood is not easy, at this time the child is more likely to want to play than the study. The most appropriate way to introduce English to young children is through an interactive game with the look and sound that contain words, numbers, and objects in the English language. Research took the example of the introduction of English language in early childhood in TAMAN KANAK-KANAK ANNISA. Recognition method used was still manually, use English textbooks and teaching aids in the form of images and text. Methods of data collection research are done by direct observation to study sites and interviews to the principal, teachers, and parents. Educational game application designed and constructed using analysis method waterfall, as well as applied to the smartphone and tablet android devices. The research concludes that very educational game to help teachers and parents as teaching media to introduce the English language. Results of the study suggest that applications can be continuously developed to achieve better results.Key words : Educational Game, English Language, Learning